FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Leny Septiani; Rizka Indri Arfianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Timeliness of the submission of financial statements is the most important thing because the information contained in it is needed by the parties, especially investors. Timeliness of the submission of financial statements is necessary so as not to lose its relevance. Loss of relevance can make information less useful for decision making. However, in reality there are still public companies that are late in submitting their financial reports, one of which is the property and real estate sector. The purpose of this study was to analyze the effect of profitability, leverage, firm size and audit committee meeting frequencies on the timeliness of submitting financial statements. Financial Services Authority (OJK) Regulation No. 29 /POJK.04/2016 Article 7 states that the submission of the annual financial report to OJK is no later than the end of the fourth month (120 days) after the date of the annual financial report, and if it exceeds 120 days, it will be subject to sanctions, fines by PT Bursa Efe Indonesia. The object of research used is the property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2020. The results of the research using Wald's test show that the independent variables are profitability, solvency size of the company, and the number of audit committee meetings with a value of sig. one tail each of 0.095, 0.028, 0.021, 0.311 so that the first and fourth hypotheses are rejected. While the second and third variables show test results of 0.028 and 0.021 so that the second and third hypotheses are accepted. The conclusion of this study shows that solvency has a negative effect and firm size has a positive effect on the timeliness of submitting financial statements. Meanwhile, profitability and audit committee meetings have no effect on the timeliness of submitting financial reports.